Management of bi-maxillary protrusion with temporary anchorage device : Management of bi-maxillary protrusion with temporary anchorage device - Pawinru, Ardiansyah S.; Asjad, A. Arigoh (Makassar Dental Journal PDGI Makassar, 2025)
Bimaxillary protrusion is a malocclusion characterised by the proclination of the upper and lower incisors and an increase in lip inclination, resulting in a convex facial profile and aesthetic imbalance. This article discusses the role of temporary anchorage devices (TADs) as an alternative absolute anchorage in the orthodontic management of bimaxillary protrusion, particularly in severe cases. The study was conducted based on various scientific literature and relevant case reports compiled in accord-ance with PRISMA. The study shows that TADs are more effective than conventional anchorage devices such as headgear in maintaining molar stability and producing better skeletal, dental, and soft tissue changes. It is concluded that TADs are a modern solution in orthodontics that can address the challenge of anterior tooth retraction without losing posterior anchorage and be-come a new standard in the management of bimaxillary protrusion.